Improving Student Learning Outcomes Through the Application of the Problem Based Learning Model in Natural Sciences Subjects - Ardiansyah Firman Effendi; Kristi Liani Purwanti (FITK UIN Walisongo Semarang, 2024)
The research intends to find out or describe the increase in student learning outcomes by using the Problem Based Learning (PBL) learning model in science learning with material on the properties of light in class IV MI students. Safinatul Huda Jepara. This research is a classroom action research consisting of three cycles, each cycle consisting of four stages, namely planning, implementing, observing, and reflecting. Data collection techniques used are tests, observation and documentation. While the data collection instruments used test questions, observation sheets and documents. The data analysis technique was carried out in a descriptive analytic manner. The results of the research show that the learning model of the Problem Based Learning (PBL) learning model can improve the learning outcomes of class IV MI students. Safinatul Huda. The increase in students who complete learning from Cycle I to Cycle II was 9.1% and Cycle II to Cycle III was 27.3%. This can be seen in the acquisition of completeness of student learning outcomes in Cycle I has an average of 70.9, Cycle II has an average of 74.5, and Cycle III has an average of 85.4. Students have achieved a classical KKM of 90.9%. Students who have not finished studying in cycle III will be given independent action in the form of exercises or remedies monitored by the teacher so that it is hoped that all students can complete it.